Hematological Parameters as Diagnostic Factors: Correlation with Severity of COVID-19 - Dadkhah, Masoomeh; Matin, Somaieh; Safarzadeh, Elham; Rezaei, Nima; Negaresh, Mohammad; Salehzadeh, Hossein; Matin, Samira; Sharifiazar, Amirhossein; Abazari, Malek (Acta Biomedica Atenei Parmensis, 2022)
Bachground and aim: Coronavirus disease 2019(COVID-19), which is the pandemic of 21st century, is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Prognostic factors play an essential role in predicting the patients who need more care. Therefore, the current study aimed to investigate the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) ratio as discriminated indexes in prognosis of patients with COVID‐19. Methods: Age, NLR, PLR, white blood cell (WBC), neutrophil count, lymphocyte count and platelet from 1007 hospitalized patients with COVID-19, who were admitted to two referring hospitals in Ardabil, North Western Iran. All confirmed cases divided into non-severe and severe groups. Results: 534 (53.4%) males and 473 (47.3 %) females with mean age of 52 years were enrolled in this study. Patients with severe COVID-19 have lower counts of lymphocyte, but have higher NLR, comparing to non-severe patients (P = 0.001). Conclusion: Elevated NLR can be assumed as an independent biomarker, which could provide a crucial indicator in the monitoring patients with COVID-19 on admission. Increased NLR was correlated with the severity of COVID-19. Assessment of NLR could be proposed to identify high risk individuals with COVID-19.